2003
DOI: 10.1080/1068316031000093423
|View full text |Cite
|
Sign up to set email alerts
|

The Demographic and Spatial Patterns of Recorded Rape in a Large Uk Metropolitan Area

Abstract: The present study details a social contextual analysis of 172 rapes and attempted rapes that occurred in a large metropolitan area in the UK. The main focus of the present study concerns the demographic characteristics of rape victims and offenders, including their age and ethnicity, vis-à-vis their relationship. The study also considers the geographic distribution of offences and their relationship to ethnicity and socio-economic status. Our data clearly indicate that the age of offenders is significantly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Offenders were concentrated into a narrower range with a higher proportion in their 20s and 30s. These findings mirror research into homicide (Cooper & Smith, 2011;Francis et al, 2004), sexual offending (Greenall & West, 2007;Muir & Macleod, 2003), and sexual homicide (Gerard et al, 2007;Greenfeld, 1997;Häkkänen-Nyholm et al, 2009). More specifically, they support previous research (Shackelford, 2002) that found young, reproductive-aged females to be over-represented as victims of sexual homicide, whereas young men were similarly over-represented among offenders.…”
Section: Demographicssupporting
confidence: 83%
See 1 more Smart Citation
“…Offenders were concentrated into a narrower range with a higher proportion in their 20s and 30s. These findings mirror research into homicide (Cooper & Smith, 2011;Francis et al, 2004), sexual offending (Greenall & West, 2007;Muir & Macleod, 2003), and sexual homicide (Gerard et al, 2007;Greenfeld, 1997;Häkkänen-Nyholm et al, 2009). More specifically, they support previous research (Shackelford, 2002) that found young, reproductive-aged females to be over-represented as victims of sexual homicide, whereas young men were similarly over-represented among offenders.…”
Section: Demographicssupporting
confidence: 83%
“…More specifically, they support previous research (Shackelford, 2002) that found young, reproductive-aged females to be over-represented as victims of sexual homicide, whereas young men were similarly over-represented among offenders. Most homicides were intra-racial, which again reflects research into homicide (Cooper & Smith, 2011; Francis et al, 2004), sexual offending (Muir & Macleod, 2003), and sexual homicide (Chan, Myers, & Heide, 2010; Greenfeld, 1997; Grubin, 1994; Van Patten & Delhauer, 2007). Therefore, in relation to the basic demographics, adult male-on-female stranger sexual homicide appears typical when compared with other crimes.…”
Section: Discussionmentioning
confidence: 72%